2022
DOI: 10.1101/2022.01.12.476023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pericentrin is a Kinesin-1 Activator that Drives Centriole Motility

Abstract: Centrosome positioning is essential for their function. Typically, centrosomes are transported to various cellular locations through the interaction of centrosome nucleated microtubules with motor proteins. However, it remains unknown how centrioles migrate in cellular contexts in which centrioles do not nucleate microtubules. Here, we demonstrate that during interphase inactive centrioles move directly along the noncentrosomal microtubule network as cargo for the motor protein Kinesin-1. We identify Pericentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…As KV cells progress from a mesenchymal to epithelial-like state, the centrosome transforms into a basal body responsible for cilium assembly in a subset of KV progenitor cells before rosette formation 15 . The centrosome has been documented to decrease its MTOC function when required to reposition where it can transport along pre-existing MTs to get to its future site of function 45,46 . Thus, KV cells may need to maintain an additional MT based structure, cytokinetic bridge derived MTs, to assist in a mesenchymal to epithelial transition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As KV cells progress from a mesenchymal to epithelial-like state, the centrosome transforms into a basal body responsible for cilium assembly in a subset of KV progenitor cells before rosette formation 15 . The centrosome has been documented to decrease its MTOC function when required to reposition where it can transport along pre-existing MTs to get to its future site of function 45,46 . Thus, KV cells may need to maintain an additional MT based structure, cytokinetic bridge derived MTs, to assist in a mesenchymal to epithelial transition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both centrosome and centriole cohesion are mediated by a small set of proteins including CDK5RAP2 (45,46) and can be monitored by staining for pericentrin, a marker for the pericentriolar material (73). Pericentrin has also been shown to interact with kinesin-1 to drive centriole motility (49). Given the reported links between Rab phosphorylation, motor adaptor protein recruitment and microtubule-mediated transport processes (53,74,75), it will be interesting to determine whether the LRRK2-mediated cohesion deficits are due to a similar phospho-Rab/motor protein interaction which is followed by inappropriate microtubule-mediated transport.…”
Section: Discussionmentioning
confidence: 99%
“…Upon centriole duplication in S phase of the cell cycle, the two centrosomes are held together by a process called centrosome cohesion, and both centriole and centrosome cohesion are mediated by a common set of linker proteins (45)(46)(47)(48)(49)(50). We have previously shown that mutant LRRK2 causes centrosomal cohesion deficits which are dependent on the presence of RILPL1 and Rab10 in a variety of cell types in vitro (42,43,51).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Kinesin-1 could either transport Polo or some PCM components away from active centrosomes. In this regard and interestingly, a recent work has reported that in Drosophila neuroblasts and squamous epithelial cells, Khc interacts directly with the PCM organizer Pericentrin-like protein (Plp) but also that Kinesin-1 is required for a differential distribution of Polo between the two centrosomes of a mitotic spindle (Hannaford et al, 2022). An attractive model would be that the PCM removed by Kinesin at the centrosomes is recycled to the previously described non-centrosomal MT sources in the oocyte, i.e the nucleus (Tissot et al, 2017) and the anterior cortex (Nashchekin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%